2011
DOI: 10.1177/0091552110394831
|View full text |Cite
|
Sign up to set email alerts
|

If I Knew Then What I Know Now: Using the Leadership Competencies Developed by the American Association of Community Colleges to Prepare Community College Presidents

Abstract: Although much has been written about preparing community college leaders, little is known about how presidents believe they might have better prepared for the role. Using presidential narratives from a national study, this article describes how presidents perceive gaps in prior preparation and offers recommendations to support the professional development of future leaders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 12 publications
2
28
0
2
Order By: Relevance
“…The other four continue to serve in their first presidency. In contrast 190 D. E. McNAIR to prior research (McNair et al, 2011), participants indicated they felt well prepared for their presidency, in part, because the tap on the shoulder allowed them to first consider their long-term career aspirations, make a decision to pursue a presidency, then intentionally fill any gaps in their preparation. While they felt well prepared, the tenure of four participants was less than state and national averages.…”
Section: Areas For Further Studymentioning
confidence: 71%
See 1 more Smart Citation
“…The other four continue to serve in their first presidency. In contrast 190 D. E. McNAIR to prior research (McNair et al, 2011), participants indicated they felt well prepared for their presidency, in part, because the tap on the shoulder allowed them to first consider their long-term career aspirations, make a decision to pursue a presidency, then intentionally fill any gaps in their preparation. While they felt well prepared, the tenure of four participants was less than state and national averages.…”
Section: Areas For Further Studymentioning
confidence: 71%
“…Multiple pathways lead to a community college presidency (Amey, VanDerLinden, & Brown, 2002;Kubala & Bailey, 2001;McNair, Duree, & Ebbers, 2011;Weisman & Vaughan, 2002, 2007. While the traditional path to the presidency has been through academic positions, such as department chair, academic dean, and chief academic officer (Amey et al, 2002), this pipeline is changing as faculty either retire (Cejda & Murray, 2010) or decide not to pursue administrative positions.…”
mentioning
confidence: 99%
“…The American literature contains numerous warnings about the impending retirement of ageing baby boomer leaders and the need for leadership development and succession planning (Ebbers, Conover, and Samuels 2010;FultonCalkins and Milling 2005;McNair, Duree, and Ebbers 2011;Plinske and Packard 2010;Reille and Kezar 2010;Scott and Johnson 2011;Wallin 2006;Sullivan 2001). Human resource issues such as recruitment, retention and personnel planning figure quite strongly.…”
Section: Human Resource Issuesmentioning
confidence: 99%
“…A key point implicit in these six core competencies is that leadership is developed not only through the formal training of leadership courses, but, like a number of studies, draws attention to the importance of informal experiential learning, mentoring and job shadowing in developing leadership capabilities (Hassan, Dellow, and Jackson 2010;McNair, Duree, and Ebbers 2011;Romano, Townsend, and Mamiseishvili 2009). Much of the literature in the last few years has focused on these six core competencies which have been well-accepted (Duree and Ebbers Research in Post-Compulsory Education 405 2012; Hassan, Dellow, and Jackson 2010;Haynes 2009;McPhail, Robinson, and Scott 2008;Sinady, Floyd, and Mulder 2010;Romano, Townsend, and Mamiseishvili 2009;Wallin 2012).…”
Section: Leadership Competencies and Their Developmentmentioning
confidence: 99%
“…Problem Statement: Knowledge management literature has highlighted the need for knowledge generation, transfer and retention in particular, the need to devise proactive measures to address the potential acute shortages of research leadership in higher education worldwide in general, and in SAHEIs in particular (Levine, 2008;Carman, Leland & Wilson, 2010;Robinson, Carrillo, Anumba & Patel, 2010;McNair, Duree & Ebbers, 2011). These fissures in research leadership are exacerbated by an apparent disjuncture between the retention rate of senior academics (e.g.…”
Section: Introductionmentioning
confidence: 99%